Dekonstruksi Pendidikan Progresif Perspektif Filsafat Islam: Menjawab Tantangan Dehumanisasi Pendidikan Kontemporer - Hidayah, Putri Nurul (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2025)
Progressive education in the modern Western tradition emphasises the liberation, independence, and experiences of learners as the core of learning. Still, in practice, it often falls into dehumanisation, where learners are reduced to objects of technocratic measurement, thus triggering a crisis of educational meaning. This study aims to deconstruct the concept of modern progressive education from the perspective of Islamic philosophy, emphasizing humanistic and transcendental values as its primary foundation. Using a qualitative-descriptive method with a philosophical hermeneutic approach, this study analyses Western and Islamic educational philosophy texts, identifies signs of dehumanisation, and reinterprets the concept of progressivism within the framework of monotheism, morality, and social responsibility. The research findings indicate that progressive education, as informed by Islamic philosophy, prioritizes the freedom of thought and the development of individual potential in conjunction with the principle of the oneness of God, thereby combining intellectual, moral, and spiritual dimensions. The hermeneutic analysis reveals that the crisis of dehumanisation can be overcome by repositioning educators as guides who play a role in guiding tazkiyah al-Nafs, integrating learning with character formation and divine awareness. This approach yields an educational model that celebrates humans holistically, rather than merely assessing cognitive achievements. The conclusion of the study emphasizes the need to develop an educational system based on Islamic values that are operational in the curriculum, methods, and evaluation, so that progressive education can function as an instrument of true liberation that maintains human dignity and honor amidst the current trend of technocratization in modern education.